Challenges Encountered by Elderly Patients on their Medications: Basis for Development of Medication Application system - Mary Joy B. Delin; Alexandra M. Cracicas; Mark Daniel A. Gerance; Nicko A. Magnaye; Glend P. Binay (International Journal of Natural and Health Sciences, 2023)
Challenges Encountered by Elderly Patients on their Medications in Bongabong Oriental Mindoro: Basis for Medication Application aimed to investigate the challenges faced by elderly patients in connection to their medication management in Bongabong, Oriental Mindoro. A quantitative research approach was employed, involving a self-administered survey questionnaire distributed to a convenience sample of elderly patients in Bongabong, Oriental Mindoro. The results revealed that the elderly patients generally had a positive status, with a weighted mean score of 3.90 for feeling physically healthy, 4.50 for the ability to perform daily activities independently, and 4.00 for mental well-being. However, challenges in medication management were identified, including occasional forgetfulness (weighted mean score of 2.90), confusion about dosage or frequency (weighted mean score of 3.50), and some discomfort in asking questions about medications (weighted mean score of 3.90). The effectiveness of technology solutions in addressing these challenges yielded mixed perceptions among the respondents, with a neutral response (weighted mean score of 3.20) regarding its helpfulness in managing medications independently, agreement (weighted mean score of 3.50) on improved understanding of medication instructions, and another neutral response (weighted mean score of 3.20) regarding its impact on medication adherence. These findings highlight the importance of addressing medication management challenges for elderly patients and suggest the need for tailored interventions. By developing targeted solutions such as medication reminders, simplified instructions, patient education, and improved communication, healthcare professionals, policymakers, and technology developers can enhance medication management, improve the quality of care, and ensure medication safety for the elderly population in Bongabong, Oriental Mindoro.